Trans/forming the Greek theatrescape: Translation for performance as representation - Vasiliki Misiou (JoSTrans: The Journal of Specialised Translation)
This paper explores the translation and staging of Paloma Pedrero’s La llamada de Lauren… in Greece (2017–2019). The play was staged at a time marked by conflicting forces: on the one hand, Greece was taking significant steps forward for transgender people, recognising basic rights and freedoms, and on the other, discriminatory practices and gender-based violence were still a very present reality. In this context, Fenia Apostolou, a director who made headlines with her story as a trans person, and Maria Hatziemmanouil, a well-known translator of Spanish theatre, decided that it was the right time to stage Pedrero’s play. Based on the agenda pursued by the agents themselves, as reflected in the paratextual materials studied, the present paper discusses the role of translation for performance in going against prevailing normative practices and constraints, ultimately effecting change. The study shows that Hatziemmanouil sees translation as a performative, transcultural, and political practice. Thanks to her translation and Apostolou’s staging, systemically underrepresented groups have become more visible, and the discussion regarding gender, sex(uality) and identity in Greece has been enhanced, proving that translation and/for performance can contribute to the trans/formation of perceptions and major changes in societies.